Innovative Variation in the Morphological Characteristics of Carbon Nanowalls Grown on a Molybdenum Disulfide Interlayer - Kim, Chulsoo; Kim, Kangmin; Kwon, Seokhun; Kang, Hyunil; Hong, Byungyou; Choi, Wonseok (Nanomaterials (Basel, Switzerland), 2022)
Carbon is a material with interesting properties which exists in large quantities on Earth, so many studies involving carbon have been conducted. In particular, nano-sized carbon allotropes, referred to as carbon nanomaterials, comprise the subject of various studies currently underway. The electrical, chemical, physical properties of carbon nanowalls (CNWs) are modified by parameters such as surface density, height and thickness. These characteristics have significant effects on CNWs and can be adjusted as a growth interlayer. It was confirmed that the molybdenum disulfide (MoS2) interlayer synthesized in this paper by radio frequency (RF) magnetron sputtering altered the morphological characteristics of the CNWs, including its shaped edge, pores diameter and density. We provide interesting results through FE-SEM, EDS and Raman analysis in this paper. Based on the Raman analysis, both the D-peak of carbon and the ID/IG ratio decreased. Through this study, the effect of MoS2 on the morphological characteristics of CNWs was confirmed.